Development of a Global Index Measuring National Policy Commitments to HIV Prevention and Treatment among People Who Inject Drugs - Amini, Mohamad Reza (2020)
Background: People who inject drugs (PWID) around the world are disproportionately affected by the HIV epidemic. National policy responses to the epidemic heavily influence risk factors for HIV acquisition among this key group. Prior efforts to monitor national policy responses to HIV/AIDS among PWID were limited both in scope and coverage. In this paper we develop and validate the HIV-PWID Policy Index (HPPI) to benchmark and monitor national commitments to HIV prevention and treatment among PWID. Methods: Composite indicator was constructed employing fuzzy multilayer data envelopment analysis (FMLDEA). Model inputs based on data from 105 countries included 27 variables measured across six conceptual domains, including needle and syringe programs, opioid substitution treatment, testing and counseling, information and education, monitoring and evaluation, and legal and policy climate. Results: According to the HPPI, the top performing countries in commitment to HIV prevention and treatment among PWID were Spain (0.988), Switzerland (0.982), Luxembourg (0.970), Moldova (0.970), and Kyrgyzstan (0.945), whereas the poorest performing included Nicaragua (0.094), Japan, (0.094), Cape Verde (0.097), Syria (0.174), and Benin (0.185). Regionally, commitment to HIV services targeting PWID was highest among European countries (0.81) and lowest among African countries (0.50), with Oceania (0.76), Asia (0.66), and the Americas (0.56) in the mid-range. Subregional differences were even more prominent, with West and Central European nations (0.84) and Central American nations (0.22) earning the highest and lowest HPPI scores, respectively. Conclusions: The HPPI documented substantial national and regional variation in policy responses to the HIV epidemic among PWID. Our analysis also revealed that many countries have limited HIV/AIDS data collection and monitoring capabilities. Continued enhancement and standardization of global HIV/AIDS monitoring efforts are therefore vital to articulated national and international benchmarking and performance assessment goals